Illusion of stability: An empirical analysis of inflation data manipulation by russia after 2022 - Alex Plastun; Anna Vorontsova; Yaroslava Slyvka; Olha Yatsenko; Liudmyla Huliaieva; Victor Sukhonos; Ruslan Bilokin (Public and Municipal Finance)
This paper explores the perceived resilience of russia’s economy under severe sanctions, investigating the potential falsification of economic data to demonstrate the growth. The hypothesis is that the relationship between the official inflation rate and the FMCG deflator index during 2019–2021 significantly differs from that of 2022–2024. Statistical methods, such as correlation analysis, Granger causality tests, and differences tests (e.g., t-tests and Wilcoxon tests), are used along with vector autoregressive (VAR) models and robust linear regressions. The study covers the pre-invasion period (2019–2021) and the post-invasion period (2022–2024), focusing on indicators like the official inflation rate, inflation expectations, CPI, and the FMCG deflator index. Findings reveal a shift from a direct to an inverse correlation between official inflation and the FMCG deflator post-2022, suggesting data manipulation. Pre-2022 models predict inflation 2-3 times higher than both post-2022 models and official statistics, raising concerns about the reliability of russia’s economic data. Further research should explore indirect metrics, such as electricity production and cargo shipments, for additional evidence of data falsification. AcknowledgmentsAlex Plastun gratefully acknowledges financial support from the New Europe College (NEC), the Center for Advanced Study, and Sumy State University.Anna Vorontsova gratefully acknowledges financial support from Sumy State University.